The Influence of Price and Service Quality on The Satisfaction of Italian Tourists (Case Study Pt. Bali Prima Holidays) - I Komang Krisna Putra Yasa; Ni Putu Evi Wijayanti; Made Darmiati (Politeknik Pariwisata Bali, 2024)
This study aims to analyze the effect of price and service quality on the satisfaction of Italian tourists who buy Bali Round Trip tour packages at PT. Bali Prima Holidays. This consider uses quantitative strategies with information collection through surveys conveyed to 107 Italian traveler respondents. Data analysis was carried out using multiple linear regression with the help of SPSS software version 26. The findings demonstrated that Italian tourist satisfaction was positively and significantly impacted by price and service quality. The price variable has a t value of 16,088 with a significance of 0,000, while the service quality variable has a t value of 3,270 with a significance of 0,001. Simultaneously, price and service quality have a calculated F value of 652,061 with a significance of 0,000, which means that the two variables jointly affect tourist satisfaction with a contribution of 92,5% (Adjusted R2). This study concludes that increasing competitive prices and good service quality can increase Italian tourist satisfaction. It is recommended to PT Bali Prima Holidays to evaluate prices and improve modern facilities and equipment to increase tourist satisfaction.